Motion verbs in vietnamese and english (Ensino em Perspectivas, 2025)
To help students specialize languages in depth, comparing the similarities and differences between languages is necessary. The purpose of this article is to compare motion verbs in Vietnamese and English to see the similarities and differences. To achieve the goal, the author will research the theoretical basis, clearly pointing out the similarities between omnidirectional verbs in Vietnamese and English; differences in the conjugation ability of Vietnamese and English polytransitive verbs; and the possibility to apply it to teaching students. From research, the author will focus on providing discussions on this issue.